Pengaruh Viral Marketing Dan Neuromarketing Terhadap Keputusan Pembelian Cromboloni Roti'o Di Cabang Manhattan Square Medan - Rahmaini, Rahmaini; Salqaura, Siti Alhamra (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
The purpose of this study was to determine the effect of Viral marketing on purchasing decisions, to determine the effect of Neuromarketing on purchasing decisions (3) test the effect of Viral marketing and Neuromarketing on purchasing decisions for Cromboloni Roti'O at Manhattan Square Medan Branch. This research method uses an associative research type quantitative approach. By distributing questionnaires to Cromboloni Roti'O at Manhattan Square Medan Branch. The population in this study was the Medan Sunggal sub-district of 131,741 people. And the sample in this study used the slovin formula, namely 100 respondents, the data analysis technique used multiple linear regression. With the results of the study. (1)Viral marketing (X1) has a positive and significant influence on purchasing decisions (Y) as evidenced by t-count t table (6.575 1.983) and a significant value (sig) (0.000 0.05) Neuromarketing(X2) has a positive and significant influence on purchasing decisions (Y) t-count t table (6.575 1.983) and a significant value (sig) (0.000 0.05). Viral marketing (X1) Neuromarketing (X2) together (simultaneously) has a positive and significant effect on purchasing decisions. Evidenced by f-count of, 167.832 and f-table value of 2.386 and a significance value of 0.000, smaller than alpha 0.050.